Effectiveness of Atropine Sulfate and Diazepam in Organophosphate Poisoning in Remote Area: A Case Report - Junapati, I Kadek Ludi; Pratama, Fabianus Anugrah (Solo Journal of Anesthesi, Pain and Critical Care (SOJA), 2024)
Background: Organophosphate poisoning is a significant public health concern in developing countries, including Indonesia, largely due to the widespread use of pesticides and insecticides. These chemicals, while effective for agricultural purposes, have been linked to severe health issues, including acute poisoning. One of the major health risks associated with organophosphate exposure is its potential link to suicide attempts. The toxic effects of organophosphates primarily stem from their inhibition of acetylcholinesterase, an enzyme crucial for the proper functioning of the nervous system. This inhibition leads to the accumulation of acetylcholine, resulting in overstimulation of the nervous system. Managing organophosphate poisoning poses a considerable challenge, particularly in remote areas where access to specific antidotes is limited. Case Illustration: A 17-year-old female high school student presented to the emergency room of the Boawae Primary Health Care Center with a major complaint of decreased consciousness, as evidenced by a Glasgow Coma Scale (GCS) score of 9/15. The patient had no prior history of neurological or psychiatric disorders. It was suspected that the patient had attempted suicide by ingesting pesticides approximately 60 minutes prior to admission. At the time of admission, she exhibited symptoms including nausea and vomiting, which had progressively worsened. Upon examination in the emergency room, the patient displayed increased saliva production and pinpoint pupils. In response to these symptoms, the medical team administered intravenous Diazepam and Atropine Sulfate, continuing treatment until atropinization was achieved. Conclusion:  In managing organophosphate poisoning, particularly in remote regions with limited access to specific antidotes, Atropine Sulfate and Diazepam represent viable alternative treatment modalities. These treatments can effectively counteract the toxic effects of organophosphates and achieve necessary atropinized conditions to stabilize the patient’s condition.